The Influence of the Documentary Film Script “Di Atas Rel Mati” on Public Empathy and Interest in Watching Documentary Films - Susana Susana (Sean Institute, 2026)
The documentary film Di Atas Rel Mati portrays the lives of students who study at Master School and the challenges they face due to the partial eviction of the school area by the government for the construction of integrated Jakarta city transportation infrastructure. In order for this film to be effectively conveyed to the audience, it must be supported by a well-developed scenario. A scenario that is clearly delivered can provide stimuli that evoke immediate emotional responses from the audience. The quality of a strong documentary film scenario has the potential to enhance public empathy toward the residents of Master School. This study aims to examine the effect of the documentary film scenario Di Atas Rel Mati on public empathy. The research involved 130 respondents selected through random sampling. The study employed a quantitative research approach using descriptive and verificative methods, with multiple linear regression analysis as the data analysis technique. The results indicate that cinematography, sound system, and resource persons jointly contribute 30.2% to the formation of public empathy, while the remaining 69.8% is influenced by other variables not examined in this study. A high-quality scenario is determined by effective cinematography, an appropriate sound system, and suitable resource persons. The better the quality of the scenario, the greater its potential to enhance public empathy.